EXPLORATION OF BROTH CHICKEN GUT AS GROWTH MEDIA OF Escherichia coli BL21 pET-Endo FOR ENDO-Β-1,4-D-XYLANASE PRODUCTION - Anak Agung Istri Ratnadewi; Moch. Yoris Alidion; Agung Budi Santoso; Ika Oktavianawatia (ALCHEMY Jurnal Penelitian Kimia, 2017)
Endo-β-1,4-D-xylanase is a hydrolytic enzyme that breakdown the 1.4 chain of xylan polysaccharide. We have succes to transform the plasmid pET-Endo gene encoding endo-1,4-β-D-xylanase from Bacillus sp. originally from termites abdominal to E. coli BL21. The clone was ready for large scale of enzyme production. To reduce production cost, we look for subtitute media for the expensive Luria Berthani broth. Chicken guts broth is good alternative while rich of protein and very cheap. The content of N dissolved chicken guts broth reaches 87 % of LB broth. Growth of E. Coli BL21 in Chicken guts broth and LB broth (as control) was observed by Optical Density (OD) using spectrofotometer. Concentration of glucose added in broth and incubation temperature was varied. The result showed that optimal growth was in addition of 1.5 % glucose and incubated at  37 oC for 16 h. This optimal condition was used to grow E. coli BL21 pET-Endo for xylanase production. Enzyme purification was done by Ni-NTA affinity chromatography. Highest protein yield was 0.076 mg/mL obtained in 100 mM imidazole elucidation. The activity and specific activity of xylanase were estimated as 0.042 U/mL and 0.556 U/µg, respectively. The purification factor was 3.16 time and the molecular weight of enzyme was ± 30, 000 Dalton